Dollarization and Semi-Dollarization in Ecuador - Beckerman, Paul (World Bank, Washington, DC, 2014)
Over the 1980s and 1990s, GDP growth had stagnated because of oil export price volatility and natural disasters, the sacrifice of capital formation to heavy external public debt service, and incomplete and uneven structural reform. The exchange rate depreciation that proved continually necessary to sustain the net-export surplus and limit external debt accumulation induced Ecuadorians to dollarize spontaneously. The 1998 shocks affected real economic activity--hence bank loan portfolios, and widened the fiscal and current acccount deficits. The external imbalance led to exchange rate depreciation. Dollar-denominated bank loans whose borrowers lacked dollar income increasingly turned non-performing. At the same time, the depreciation swelled the locla currency value of dollar deposit liabilities. Many depositors, fearing that banks had become unsafe, withdrew, and over 1999 the Central Bank had to provide banks massive liquidity support. By year's end, the resulting monetary issue led to the exchange rate collapse and incipient hyperinflation that forced the move to full dollarization. Ecuador's Central Bank will continue operating, using its foreign exchange holdings to carry out limited liquidity management and lender-of-last-resort activities. Ecuador's public accounts and banking system remain vulnerable to commodity-price and natural shocks. Exchange rate adjustment and monetary expansion are no longer available, however, to manage the external accounts, accommodate the public deficit, or assist failing banks. Further structural reform remains essential to assure fiscal discipline and banking system safety.